Confined Crystallization of Spin‐Crossover Nanoparticles in Block‐Copolymer Micelles. (3rd February 2020) - Göbel, Christoph; Hils, Christian; Drechsler, Markus; Baabe, Dirk; Greiner, Andreas; Schmalz, Holger; Weber, Birgit
Abstract: Nanoparticles of the spin‐crossover coordination polymer [FeL(bipy)] n were synthesized by confined crystallization within the core of polystyrene‐ block ‐poly(4‐vinylpyridine) (PS‐ b ‐P4VP) diblock copolymer micelles. The 4VP units in the micellar core act as coordination sites for the Fe complex. In the bulk material, the spin‐crossover nanoparticles in the core are well isolated from each other allowing thermal treatment without disintegration of their structure. During annealing above the glass transition temperature of the PS block, the transition temperature is shifted gradually to higher temperatures from the as‐synthesized product ( T 1/2 ↓=163 K and T 1/2 ↑=170 K) to the annealed product ( T 1/2 ↓=203 K and T 1/2 ↑=217 K) along with an increase in hysteresis width from 6 K to 14 K. Thus, the spin‐crossover properties can be shifted towards the properties of the related bulk material. The stability of the nanocomposite allows further processing, such as electrospinning from solution. Abstract : Spindoktor : Die Synthese und Charakterisierung von Spin‐Crossover‐Nanopartikeln mit verbesserten Spin‐Crossover‐Eigenschaften in einer Blockcopolymer‐Matrix ergibt ein Spin‐Crossover‐Nanokomposit, das stabil genug für die Weiterverarbeitung z. B. durch Elektrospinnen ist.